Penerapan Semitic Rhetorical Analysis (SRA) Pada Surah Al-Qiyamah - Asnawi, Aqdi (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2018)
Nicolai Sinai has criticized the method of Qur’anic structural analysis offered by Michel Cuypers due to his arbitrary mode of cutting verses and neglecting rhyme of the Qur’an. This paper, then, attempts to apply the method, which is called as Semitic Rhetorical Analysis (SRA), into surah al-Qiyamah by concerning the waqf of the verses. The purpose of this study is to determine whether the structure of surah al-Qiyamah is coherent and consistent to the pattern of text composition in Semitic Rhetoric analysis. This paper argues that there are parallel, concentric, or mirror symmetrical composition patterns at various levels of text based on Semitic Rhetoric principles. The structure of the surah, then, shows its coherence and thus, opposes to the notion of the existing of some irrelevant verses in this surah.